International health and nutrition - a human rights perspective - Westaway, Jennifer (Kagawa Nutrition University, KNU, 2008)
The role of human rights in addressing public health issues within the framework of international health has largely been ignored by mainstream research. It is contended that this is a key problem and that human rights can and should play a more significant role in addressing the issue of nutrition. The key objective of my research in the area of human rights and international health has been to identify the role which the international law can play in addressing ongoing crises in international health. Specifically, I examined such documentation as the Universal Declaration on the Rights of the Child, as well as many related documents, to ascertain rights and responsibilities of signatory states with respect to the provision of basic health care. I also examined the role and statements of the WHO and the World Bank. Finally, I conducted several case studies looking at varying international jurisdictions, to assess legal approaches to varying public health needs. My research concluded firstly, that public health crises, to be addressed from an international law perspective, require a refocusing of attention allowing them to be viewed as violations of obligations by signatory states. Secondly, my research identified an almost universal lack of willingness by courts to intervene in government resource allocation decisions, which impact directly on how public health expenditure occurs. Thirdly, my research revealed a lack of a co-ordinated, cross sector approach to the solving of key public health issues.It is therefore my conclusion that by addressing fundamental health needs from a human rights perspective, the understanding of the obligations which arise under international conventions, and violations thereof, will provide those working within the field of public health with a valuable tool with which to counter arguments from governments that they are meeting their obligations.